Reconstruction of a Normative Regulatory Model for Juvenile Cybercrime within the Indonesian Criminal Justice System: A Restorative and Procedural Approach - Yuni Priskila Ginting; Franciscus Xaverius Wartoyo; Anissa Furqanina (Journal of Law and Social Politics, 2026)
Background: The rapid development of digital technology has generated new forms of cybercrime involving children as perpetrators. In Indonesia, existing legal frameworks, particularly the Criminal Code and Law No. 11 of 2008 on Electronic Information and Transactions, have not fully accommodated the dual position of children as offenders and subjects entitled to special protection. Objective: This study aims to reconstruct a regulatory model for cybercrimes committed by children based on restorative justice and the best interests of the child. Methods: This study applies a normative juridical method using statutory, conceptual, and comparative approaches. It examines Indonesian regulations, relevant doctrines, international child protection standards, and comparative legal frameworks from the United Kingdom, Australia, and Malaysia. Results: The findings show that Indonesian law remains largely retributive and lacks specific procedural guidelines for digital offenses involving minors. The proposed model emphasizes child-sensitive digital forensic procedures, diversion mechanisms, digital rehabilitation programs, and harmonization between the ITE Law and the Juvenile Criminal Justice System Law. Conclusion: The proposed framework integrates criminal liability, child protection, restorative justice, and digital literacy. Future research should empirically test this model through field studies involving legal practitioners and juvenile court data.